School-Based Interventions for The Prevention Of Anemia Among Adolescent Girls: A Literature Review - Ni Komang Tri Agustini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Anemia is a big health issue among adolescent girls particularly in developing countries, with serious consequences for growth, cognitive function, and overall well-being.Objective: to examine the effectiveness of various intervention for anemia prevention in school setting among adolescent girl Methods: A comprehensive literature search was conducted using Google Scholar, PubMed, EBSCO with relevant keywords in both English and Bahasa Indonesia. The included studies utilize different methodologies, such as quasi-experimental, participatory action research (PAR), and media development using Analysis, Design, Development, Implementation and Evaluation (ADDIE) Results: The findings consistently demonstrate that educational interventions, particularly those utilizing digital and interactive media, effectively enhance knowledge, foster positive attitudes and promote health behaviors Conclusion: To maximize effectiveness, future programs should expand the use of digital platforms. Additionally, integrating culturally relevant and community based educational strategies can further enhance the long-term impact of anemia prevention efforts among adolescent girls